Effect of rice bran oil or coconut oil on in vitro carbohydrate and protein digestion of cooked fragrant rice - Tanjor, Siriporn; Hongsprabhas, Parichat (Agriculture and Natural Resources, 2021)
RESOURCESThe influences were investigated of rice bran oil (RBO) or coconut oil (CO) on the digestion of cooked rice having different final lipid contents (0.07–7.32% dried weight basis). Cooked rice was ground for 10 s or 300 s to represent different degrees of mastication. The rice ground for 10 s had a lower surface area than the rice ground for 300 s and retained the amyloid-like network of protein and non-starch carbohydrate in the endosperm cell wall. Grinding rice for 10 s released glucose up to 80% of the carbohydrate while rice ground for 300 s released glucose of only 60% during in vitro digestion for 152 min. Although the oil type and concentration did not significantly (p ≥ 0.05) affect the release of glucose from rice ground for 300 s, principal component analysis suggested that RBO lowered the release of glucose from rice ground for 10 s due to the high contents of phytosterols and long-chain fatty acids. Rice cooked in the presence of RBO or CO and ground for 300 s released the NH2 group during the late intestinal phase to a greater extent than rice cooked in water alone. The interplay among the integrity of the amyloid-like network in the endosperm cell wall resulting from different degrees of mastication or grinding time, together with the oil type and contents during rice cooking, the digestion of rice proteins and the surface-active nutrients released during digestion in the presence of bile extracts, were significant (p < 0.05) in the release of glucose from cooked rice.